From Tradition to Modernity: Traces of Jami'at Khair and Al-Irsyad in Indonesian Islamic Education - Hilmi Nur Sayyida; Kamalia Alda Ramadhani; Muhammad Zidan Akyas; Sutrimo Purnomo (Aslim: Journal of Education and Islamic Studies, 2026)
Islamic educational institutions played an important role in the development of education and the renewal of Islamic thought in Indonesia, especially during the early twentieth century when various reform movements emerged in social, religious, and educational fields. Among the influential organizations were Jami’at Khair and Al-Irsyad Al-Islamiyyah, which established educational institutions to meet the Muslim community’s need for a more organized and modern educational system while maintaining Islamic values. Both organizations introduced reforms in teaching systems, curriculum development, and the management of Islamic education in order to adapt to the changing times. This study aims to examine the background of the establishment of Jami’at Khair and Al-Irsyad educational institutions, the educational systems implemented, and their contributions to the development of Islamic education in Indonesia. The research employed a qualitative method with a historical approach through library research using books, journals, and historical documents as sources. The findings show that both institutions played a major role in the modernization of Islamic education through the implementation of more structured educational systems, the integration of religious and general sciences within the curriculum, and the application of more systematic and rational teaching methods. Furthermore, these institutions contributed to shaping a generation of Muslims with strong religious understanding, open-minded perspectives, and the ability to adapt to social and intellectual developments of their time.